2016
DOI: 10.1038/srep30981
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of aggressive behaviour in chicken

Abstract: In the poultry industry, aggressive behaviour is a large animal welfare issue all over the world. To date, little is known about the underlying genetics of the aggressive behaviour. Here, we performed a genome-wide association study (GWAS) to explore the genetic mechanism associated with aggressive behaviour in chickens. The GWAS results showed that a total of 33 SNPs were associated with aggressive behaviour traits (P < 4.6E-6). rs312463697 on chromosome 4 was significantly associated with aggression (P = 2.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 48 publications
2
22
0
Order By: Relevance
“…Biscarini et al [ 6 ] investigated the genetic architecture of direct and indirect genetic effects of plumage condition in laying hens and found a SNP in the HTR2C gene, which is involved in the serotonergic system, that was associated with indirect genetic effects. Another study on aggression in chickens revealed a role of the dopaminergic system [ 29 ]. Moreover, Bolhuis et al [ 30 ] investigated the effects of group selection on survival on serotonin levels and suggested that the level of serotonin may be linked to the development of cannibalism.…”
Section: Resultsmentioning
confidence: 99%
“…Biscarini et al [ 6 ] investigated the genetic architecture of direct and indirect genetic effects of plumage condition in laying hens and found a SNP in the HTR2C gene, which is involved in the serotonergic system, that was associated with indirect genetic effects. Another study on aggression in chickens revealed a role of the dopaminergic system [ 29 ]. Moreover, Bolhuis et al [ 30 ] investigated the effects of group selection on survival on serotonin levels and suggested that the level of serotonin may be linked to the development of cannibalism.…”
Section: Resultsmentioning
confidence: 99%
“…In Japanese breeds, information on innate fear is limited to the above two reports on Nagoya and Tosa-Jidori. Although aggressive behavior, leading to a large animal welfare issue, has been reported in commercial male broilers ( Millman et al , 2000 ; Li et al , 2016 ), little is known about fear-related behavior in meat-type breeds, such as White Plymouth Rock, which has been used worldwide as a parental breed of commercial broilers.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the typical brain monoamine levels, we propose that aggressiveness may be related to the ADR genes based on the observed relative differences in brain NE level. Aggressiveness is determined by several genes and neurotransmitters [70][71][72][73][74][75][76] . Identification of these factors may help elucidate their modes of action.…”
Section: Discussionmentioning
confidence: 99%